Dampak Pembelajaran Daring Terhadap Minat Belajar pada Pembelajaran Tematik Bermuatan PPKn Siswa kelas IVA SDN 52 Kota Bengkulu pada Masa Pandemi - Tamara agestia; Puspa djuwita; Dalifa dalifa (JURIDIKDAS, 2022)
AbstractThis study aims to describe the impact of interest in learning on thematic learning containing PPKn for grade IVa SD 52 Bengkulu City during the pandemic. This research uses qualitative research with descriptive study method. The research subjects were homeroom teachers of IVA class, parents of students, and students of class IVA. The focus of the research is the impact of online learning on students' interest in learning. The research instrument is using observation, interview and documentation guidelines. Data collection techniques using observation, interviews and documentation. The data obtained were analyzed through Data Collection (Data Collection), Data Reduction (Data Reduction), Data Display (Data Presentation), Conclusion Drawing/verification. The results of this study are: 1). Teachers design learning independently. The RPP owned by the teacher is in accordance with the RPP component in learning management, one of which is preparing a design in accordance with Surat Edaran Mendikbud Nomor 14 Tahun 2019 tentang Penyederhanan  Rencana Pelaksanaan Pembelajaran.The thematic learning design for PPKn content owned by teachers has included online RPP components in the form of learning objectives, learning steps and learning assessment 2). The implementation of online learning carried out by teachers in thematic learning containing PPKN students in class IVA at SDN 52 Bengkulu City is going well and the steps in the online learning process carried out by teachers are in accordance with Surat Edaran Kemendikbud Nomor 15 Tahun 2020 Tentang Pedoman Penyelenggaraan Belajar darirumah Dalam Masa Darurat Penyebaran Corona Virus Disease (Covid-19.)3). This online learning has a negative impact on interest in learning in thematic learning with PPKN students.Keywords: Online Learning, Interest in Learning, PPKn Thematic Learning